GW24-e1750 The Comparison of Remedy Vascular Injury with Different Embolisation Agents in the Comprehensive Surgical Treatment Shelter. (1st October 2013) - Shibei, Li; yaling, Han
Abstract : Objectives: There is no report about embolic agent used to treat different types of vascular injury in the comprehensive surgical treatment shelter. Methods: Producing different types of vascular injury animal models in the comprehensive surgical treatment shelter, using different types of embolic agent such as gelatin sponge, sodium alginate - chitosan microspheres coil, and evaluating time of surgery, results of operations, image clarity and equipment manipulated, exploring the treatment effect. Results: 10 successful operation were performed, the success rate of 100%, 0 cases of death. DSA imaging performance and equipment operability, interventional diagnosis and treatment can effectively for performing the operation. Conclusions: It was effectiveness for using suitable embolic agent in the treatment of different types of vascular injury in the comprehensive surgical treatment shelter in disaster site or battlefield first-line.